A model study of tropospheric impacts of the Arctic ozone depletion 2011. Issue 3 (8th July 2014) - Karpechko, Alexey Yu.; Perlwitz, Judith; Manzini, Elisa
Abstract: Record Arctic ozone loss in spring 2011 occurred in concert with record positive values of the tropospheric Northern Annular Mode (NAM) index raising the question about the role of stratospheric driver on this tropospheric climate event. A set of 50 years long simulations by atmospheric general circulation model European Centre/Hamburg version 5 (ECHAM5) is carried out and the responses of the model to observed anomalies in stratospheric ozone (O3) and sea surface temperatures (SST) separately and also the response to combined SST and O3 forcing (ALL) are analyzed. In all three experiments the response is characterized by a strengthening of stratospheric polar vortex in March–April. In the ALL experiment, this strengthening is followed by a significant, long‐lasting shift of the tropospheric circulation toward a positive NAM phase and increased probability of occurrence of extremely positive NAM events. The combined effect of the O3 and SST forcings on the stratospheric circulation differs from the sum of the individual O3 and SST responses, most likely due to nonlinear effects, leading to a colder stratosphere in February–March. In the troposphere, the sum of the individual responses is comparable in magnitude to the ALL response, but the individual responses are delayed with respect to that in ALL. In summary, these results suggest that both ozone‐induced stratospheric cooling and tropospheric forcing associated with the SST anomalies contributed to the record tropospheric climate anomalies observed in spring 2011. Key Points: Arctic ozone depletion 2011 contributed to tropospheric circulation anomalies Ozone impacts are weak in isolation, but they significantly amplify SST forcing Nonlinear interactions between ozone and SST forcings implicated in the results